Chapter 12 - HPP of fruit and vegetable products: Impact on quality and applications - Denoya, Gabriela Inés (2020)
Sensory characteristics of vegetables and fruits, including color, texture, and flavor, are especially vulnerable to conventional heating treatment. High-pressure processing (HPP), a nonthermal technology, has been widely applied to various fruit and vegetable products (F&VP) for different purposes in the last two decades. As a result, novel applications, the optimization and improvement of food processing operations, as well as the evaluation on related quality changes induced by HPP has been updated, although the application of this technology in F&VP has been reported before. This chapter describes the last advances in the effects of HPP on deteriorating enzymes and microbes of F&VP and the general changes of key quality parameters and nutrient components of the products. The mechanisms behind the quality changes and the applicability of HPP in selected food matrix are also discussed.